Struktur Komunitas Makrozoobenthos di Perairan Wilayah Morosari Desa Bedono Kecamatan Sayung Demak - Ulfah, Yulia; Widianingsih, Widianingsih; Zainuri, Muhammad (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
The pond area of Bedono waters become a shallow water, due to the influence of high tide (rob). This condition affect the macrozoobenthos, one of the animals that live in the area. The objective of this research is to look for the macrozoobenthos community structure of in the Region Morosari Waters, Bedono District of Sayung, Demak. Twenty five polychaeta species were found in this research, 7 species of bivalves, 6 species of gastropods and 1 species of crustacean, with abundances ranging between 36-1331 ind/m2 with diversity index value (H ') in each research ranged from 2.95 (moderate diversity level) to 0.83 (low diversity level), with evennes index (e) ranged from 0.46 (moderate evennes index) to 1.00 (high evennes index). Domination index (C) ranged from 0.15 (this value shows that no domination index) to 0.69 (this value shows that domination index).